Math, asked by amittakavle, 10 months ago

diffrentiate 〖tan〗^(-1) (x/√(1-x^2 ))w.r.t.〖sec〗^(-1) (1/(〖2x〗^2-1)) *​

Answers

Answered by shadowsabers03
4

Let,

\longrightarrow u=\tan^{-1}\left(\dfrac{x}{\sqrt{1-x^2}}\right)

Substitute,

\longrightarrow x=\sin\theta

Then,

\longrightarrow u=\tan^{-1}\left(\dfrac{\sin\theta}{\sqrt{1-\sin^2\theta}}\right)

\longrightarrow u=\tan^{-1}\left(\dfrac{\sin\theta}{\sqrt{\cos^2\theta}}\right)\quad\quad[\because\sin^2\theta+\cos^2\theta=1]

\longrightarrow u=\tan^{-1}\left(\dfrac{\sin\theta}{\cos\theta}\right)

\longrightarrow u=\tan^{-1}\left(\tan\theta\right)

\longrightarrow u=\theta

\longrightarrow\dfrac{du}{d\theta}=1\quad\quad\dots(1)

Let,

\longrightarrow v=\sec^{-1}\left(\dfrac{1}{2x^2-1}\right)

\longrightarrow v=\sec^{-1}\left(\dfrac{1}{2\sin^2\theta-1}\right)

\longrightarrow v=\sec^{-1}\left(-\dfrac{1}{1-2\sin^2\theta}\right)

\longrightarrow v=\sec^{-1}\left(\dfrac{1}{-\cos(2\theta)}\right)\quad\quad[\because\cos(2\theta)=1-2\sin^2\theta]

\longrightarrow v=\sec^{-1}\left(\dfrac{1}{\cos(\pi-2\theta)}\right)\quad\quad[\because\cos(\pi-\theta)=-\cos\theta]

\longrightarrow v=\sec^{-1}\left(\sec(\pi-2\theta)\right)

\longrightarrow v=\pi-2\theta

\longrightarrow\dfrac{dv}{d\theta}=-2\quad\quad\dots(2)

Dividing (1) by (2) we get,

\longrightarrow\underline{\underline{\dfrac{du}{dv}=-\dfrac{1}{2}}}

This is the answer to the question.

Similar questions